2023
DOI: 10.1021/acs.est.2c04903
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Generation of High-Valent Cobalt Species and Chlorine Dioxide in the Co3O4-Activated Chlorite Process: Insight into the Proton Enhancement Effect

Abstract: A Co 3 O 4 -activated chlorite (Co 3 O 4 /chlorite) process was developed to enable the simultaneous generation of highvalent cobalt species [Co(IV)] and ClO 2 for efficient oxidation of organic contaminants. The formation of Co(IV) in the Co 3 O 4 / chlorite process was demonstrated through phenylmethyl sulfoxide (PMSO) probe and 18 O-isotope-labeling tests. Both experiments and theoretical calculations revealed that chlorite activation involved oxygen atom transfer (OAT) during Co(IV) formation and proton-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 62 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…The 18 O‐isotope‐labeled PMSO 2 (C 7 H 8 16 O 18 O) is also detected in Co SA ‐BNC/PMS, which unambiguously verifies the presence of high‐valence Co species (Figure S20, Supporting Information). [ 20 ] Accordingly, the degradation efficiency is remarkably reduced when PMSO is added (Figure 3b), highlighting the primary contribution from high‐valence Co‐Oxo species in pollutant removal. [ 8f ] We also found that the consumed PMS is only 6.2% in the presence of bare PMSO (Figure S21, Supporting Information), this indicates that PMSO suppresses SMX degradation primarily by quenching the active species rather than consuming PMS.…”
Section: Resultsmentioning
confidence: 99%
“…The 18 O‐isotope‐labeled PMSO 2 (C 7 H 8 16 O 18 O) is also detected in Co SA ‐BNC/PMS, which unambiguously verifies the presence of high‐valence Co species (Figure S20, Supporting Information). [ 20 ] Accordingly, the degradation efficiency is remarkably reduced when PMSO is added (Figure 3b), highlighting the primary contribution from high‐valence Co‐Oxo species in pollutant removal. [ 8f ] We also found that the consumed PMS is only 6.2% in the presence of bare PMSO (Figure S21, Supporting Information), this indicates that PMSO suppresses SMX degradation primarily by quenching the active species rather than consuming PMS.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified that Co­(IV)O species, a powerful active species, can be formed by the oxidation of the coordination of Co and N -based ligands in the PMS system. , Thus, the degradation of TC in the Co–NC-900/PMS system may involve high-valent cobalt species. To discern this, dimethyl sulfoxide (DMSO), a scavenger for high-valent cobalt-oxo species ( k (DMSO,Co(IV)) = 2.40 × 10 6 M –1 s –1 ), was added to the degradation system and displayed a vigorous inhibitory for TC degradation (dropped from 97.3 to 14.5%), indicating that Co­(IV)O probably plays a crucial role for TC degradation in the Co–NC-900/PMS system.…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, heterogeneous catalysts have been developed for PMS activation. Recently, several Co-based heterogeneous catalysts (e.g., Co 3 O 4 , Co-doped g-C 3 N 4, and Co-SACs) have been constructed to activate PMS, and Co­(IV)O is the dominant reactive species for micropollutants degradation. For instance, a single atom Co–N 4 catalyst was prepared to activate PMS, and the generation Co­(IV)O instead of radicals exhibited selective reactivity for the oxidation of emerging micropollutants .…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure 2, Fukui function, HOMO distribution, and ESP are significantly impacted by protonation, resulting in alterations to the active site. Su et al 86 demonstrated the pivotal role of protons in the formation of high-value metals and activation of chlorite. In this process, H + can effectively reduce the energy barrier generated by Co(IV) and enhance the stability of the final product, which is defined as the "proton enhancement effect".…”
Section: Frontier Electron Densitymentioning
confidence: 99%